Integrative Characterization of the Role of IL27 In Melanoma Using Bioinformatics Analysis - Dong, Chunyu; Dang, Dan; Zhao, Xuesong; Wang, Yuanyuan; Wang, Zhijun; Zhang, Chuan (Frontiers in Immunology, 2021)
Background IL27 has been reported to play dual roles in cancer; however, its effects on the tumor microenvironment (TME), immunotherapy, and prognosis in melanoma remain largely unclear. This study was aimed to uncover the effects of IL27 on TME, immunotherapy and prognosis in patients with melanoma. Methods RNA-seq data, drug sensitivity data, and clinical data were obtained from TCGA, GEO, CCLE, and CTRP. Log-rank test was used to determine the survival value of IL27. Univariate and multivariate Cox regression analyses were employed to determine the independent predictors of survival outcomes. DAVID and GSEA were used to perform gene set functional annotations. ssGSEA was used to explore the association between IL27 and immune infiltrates. ConsensusClusterPlus was used to classify melanoma tissues into hot tumors or cold tumors. Results Clinically, IL27 was negatively correlated with Breslow depth (P = 0.00042) and positively associated with response to radiotherapy (P = 0.038). High IL27 expression showed an improved survival outcome (P = 0.00016), and could serve as an independent predictor of survival outcomes (hazard ratio: 0.32 - 0.88, P = 0.015). Functionally, elevated IL27 expression could induce an enhanced immune response and pyroptosis (R = 0.64, P = 1.2e-55), autophagy (R = 0.37, P = 7.1e-17) and apoptosis (R = 0.47, P = 1.1e-27) in patients with melanoma. Mechanistically, elevated IL27 expression was positively correlated with cytotoxic cytokines (including INFG and GZMB), enhanced immune infiltrates, and elevated CD8/Treg ratio (R = 0.14, P = 0.02), possibly driving CD8+ T cell infiltration by suppressing β-catenin signaling in the TME. Furthermore, IL27 was significantly associated with hot tumor state, multiple predictors of response to immunotherapy, and improved drug response in patients with melanoma. Conclusions IL27 was correlated with enriched CD8+ T cells, desirable therapeutic response and improved prognosis. It thus can be utilized as a promising modulator in the development of cytokine-based immunotherapy for melanoma.